TOWARDS NEW ISLAMIC RELIGIOUS EDUCATION IN TODAY’S 21ST-CENTURY LEARNING - Rahayu, Dini Puji (Proceeding of International Conference on Islamic Education (ICIED), 2022)
Islamic Religious Education faces endless A to Z challenges in the 21st century. For this reason, this study aims to understand the crucial challenges of Islamic Religious Education that are still occurring and developing in the 21st century, as well as suggestions for responding to them to be adaptable to today's 21st-century education. Library research is used to obtain data by examining various books, articles, news, and other related documents. The result of the study shows three crucial challenges to Islamic religious education. The first is the development of science and technology that leads to the separation between science and technology and Islam, various models and learning media, sources of religious information, and types of religious information needed by Muslims. The second one is related to character degradation due to the development of Western culture. While the third is intolerance and radicalism. These challenges can be met by undertaking the following efforts. Related to the first challenge, we need to implement curriculum integration, select suitable methods and media to convey the material that should also be able to help deliver Islamic teachings to students, and encourage teachers to help direct and guide students to find and analyze religious information from various sources, as well as reconsider the portion of religious information in the Islamic Religious Education curriculum according to the needs of Muslims in Indonesia. The second, bring popular culture to learning Islamic Religious Education. The third, develop Islamic Religious Education based on religious moderation.